2015
DOI: 10.1186/s13256-015-0722-5
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo cardiomyopathy caused by epinephrine-treated bee sting anaphylaxis: a case report

Abstract: IntroductionStress-induced cardiomyopathy (Takotsubo) after bee stings in patients who have received catecholamines is rare. Endogenous as well as exogenous administration of catecholamines is thought to trigger stress-induced cardiomyopathy.Case presentationA 37-year-old healthy white woman was stung by an unknown Hymenoptera that resulted in an anaphylactic reaction. Intravenous adrenaline (0.9 mg) was administered at a nearby clinic; she was transferred to our emergency room. Cardiogenic shock was diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Because of the extreme similarities between two reported pheochromocytoma‐induced TS cases, one case which was reported later was excluded . In total, 156 cases reports (107 cases with PPGL‐induced TS, 42 cases epinephrine‐induced TS, and 7 cases norepinephrine‐induced TS) constitute the patient cohort for the meta‐analysis. Among the cases included were two non‐English case reports (one case in Swedish and one in German) where enough information could be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the extreme similarities between two reported pheochromocytoma‐induced TS cases, one case which was reported later was excluded . In total, 156 cases reports (107 cases with PPGL‐induced TS, 42 cases epinephrine‐induced TS, and 7 cases norepinephrine‐induced TS) constitute the patient cohort for the meta‐analysis. Among the cases included were two non‐English case reports (one case in Swedish and one in German) where enough information could be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…In our patient, both coronary angiography at admission and pathologic study after heart transplantation did not show coronary artery stenosis or allergic thrombi, so she was less likely to be a case of Kounis syndrome. Stress induced cardiomyopathy or Takotsubo disease, could happen after insect bites too, but most reported cases happened after epinephrine injection [8][9][10]. Our patient had no symptoms of anaphylaxis and no adrenergic medication was prescribed at the time of the bee sting.…”
Section: Discussionmentioning
confidence: 92%
“…We postulate that the patient experienced more than 200 stings which stimulated an endogenous catecholamine storm with an estimated envenomation toxin volume of 60 mg (0.3 mg per sting) [ 8 ]. Murine studies revealed a marked decrease in tissue noradrenaline concentration when injected with Africanized honey bee venom, suggesting its intracellular release [ 5 ]. It is also biologically plausible that the SRC may have resulted from a direct toxic effect of the bee venom, which may precipitate vascular thromboembolic phenomenon, refractory hypotension, malignant hypertension, arrhythmias, and hypercoagulability.…”
Section: Discussionmentioning
confidence: 99%
“…These bee swarm invasions can precipitate cardiovascular and cerebrovascular events, even culminating in death [ 1 ]. The literature is not replete describing anaphylaxis-associated, stress-induced Takotsubo syndrome with only a paucity of case reports [ 3 - 5 ]. Herein, we report the first-in-Caribbean case of a middle-aged woman who experienced stress-related cardiomyopathy (SRC) after being afflicted with innumerable Africanized honey bee stings.…”
Section: Introductionmentioning
confidence: 99%